Does a balanced test form regarding selected-response and constructed-response items overcome gender gap in test scores? An analysis of the format-gender relation in the test of economic-civic competence. (December 2019) - Ackermann, Nicole; Siegfried, Christin
Studies indicate that male students outperform female students in economic literacy and that a specific item format (selected-response, constructed-response) favours either males or females. This study analyses the relationship between item format and gender in economic-civic competence using the WBK-T2 test ("revidierter Test zur wirtschaftsbürgerlichen Kompetenz"). The WBK-T2 encompasses 32 items, of which 53% have a selected-response format and 47% a constructed-response format. To answer the research questions, we used a sample of 375 Swiss high school students and ran T-tests and multiple regression analyses. Male students significantly outperformed female students in the overall test score, in the selected-response test score and in the constructed-response test score, but effect sizes are rather small. Interest in socio-economic issues predicted but did not moderate the test scores; however, prior knowledge in economics did. Our results indicate that the balanced test form of the WBK-T2 regarding selected-response and constructed-response items does overcome the gender gap in overall test scores and format-related test scores for students with prior economic knowledge. However, this does not apply for students without prior knowledge in economics. Thus, there must be other test-external variables, such as prior knowledge in economics that cause the gender gap in economic-civic competence.